High-resolution neutron and X-ray diffraction room-temperature studies of an H-FABP–oleic acid complex: study of the internal water cluster and ligand binding by a transferred multipolar electrondensity distribution. (2016) - Howard, E. I.; Guillot, B.; Blakeley, M. P.; Haertlein, M.; Moulin, M.; Mitschler, A.
No abstract available